2021
DOI: 10.3389/fenvs.2021.620125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Social Norms in Fostering Pro-Environmental Behaviors

Abstract: Human activity is changing the biosphere in unprecedented ways, and addressing this challenge will require changes in individual and community patterns of behavior. One approach to managing individual behaviors is “top-down” and involves imposing sanctions through legislative frameworks. However, of itself, a top-down framework does not appear sufficient to encourage the changes required to meet environmental sustainability targets. Thus, there has been interest in changing individual-level behavior from the “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…The perception of boundaries is not the same in the 3 ecosystem domains, leading to disparities in how people defend and protect physical areas (e.g., land, and sometimes wetlands and streams, are often in private ownership, and the ocean, and the resources it provides and sustains, are publicly owned; Figure 1B). People are more likely to adjust their actions to protect a forest or stream on their own property, or in a public space that is near to where they live, than a river or estuary that is some distance away (i.e., the psychological distance effect; Perry et al, 2021). Ecological processes transcend boundaries constructed by humans (DeFries and Nagendra, 2017), and this fractured socialecological dynamic creates barriers to identifying and acting on the drivers of change and solutions.…”
Section: Se-p2mentioning
confidence: 99%
“…The perception of boundaries is not the same in the 3 ecosystem domains, leading to disparities in how people defend and protect physical areas (e.g., land, and sometimes wetlands and streams, are often in private ownership, and the ocean, and the resources it provides and sustains, are publicly owned; Figure 1B). People are more likely to adjust their actions to protect a forest or stream on their own property, or in a public space that is near to where they live, than a river or estuary that is some distance away (i.e., the psychological distance effect; Perry et al, 2021). Ecological processes transcend boundaries constructed by humans (DeFries and Nagendra, 2017), and this fractured socialecological dynamic creates barriers to identifying and acting on the drivers of change and solutions.…”
Section: Se-p2mentioning
confidence: 99%
“…Ho et al (2020) believed that the low level of public participation in climate change may be due to the neglect of the future threat of climate change and the distant benefits of mitigation behavior, the research found that raising awareness of climate change can promote pro-environmental behavior. Social norms arised from the expectation of others' behavior and the consequences of abiding by or deviating from these norms, meta-analysis showed that social norms can promote behavior conducive to the environment (Perry et al, 2021). Gao et al (2021) analyzed the relationship between public awareness of green products and price sensitivity, and results showed that public recognition, self-explanation and time distance played an important role in predicting the price sensitivity of green products.…”
Section: Literature Co-citation Analysis and Knowledge Base Identific...mentioning
confidence: 99%
“…Next, previous surveys have predicted pro-environmental behaviors through three perspectives. The first perspective is to adopt institutional variables to explain pro-environmental behaviors, such as institutional norms (Perry et al, 2021). The second perspective is to adopt personal perceptions to explain pro-environmental behaviors (Handoyo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%